Analysis on IoT based dynamic street light control system - Srinivas, M; Naga Siva Ram, T; Kanthi Aishwarya, P; L. Priyanka, K (International Journal of Engineering and Technology, 2018)
The Dynamic street lightening system is designed for energy saving through automation, which is best ever solution for electric consumption as the manual operation for the lightening system for the smart cities is difficult to operate also because of human negligence and maintenance cost is more. Light dependent resistor is used to sense the light intensity measure and transmits the statistics to micro controller and work accordingly that is if the intensity of light increases then the light will be in off mode and if the intensity of light decreases then the light will be in on mode. Through internet connection the status of street lights can be identified through a communication channel called GSM. If at all any light fails to work then alert message is send to the mobile through GSM mobile terminal. This reduces heat emissions, power consumption, maintenance, replacement costs and carbon monoxide emissions.Â